Kajian Metoda Seleksi Penempatan Mahasiswa Baru Jalur PMDP JKL Poltekkes Depkes Yogyakarta Tahun 2008 Hubungannya dengan Prestasi Belajar - Agus Kharmayana Rubaya; Siti Hani Istiqomah; Maryana Maryana (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
In 2008, The Department of Environmental Health of Yogyakarta Polytechnic of Health, to conduct the selection process on the new enrolments from PMDP entry-pathway employed three types of tests, i.e. TOEFL, Academic Potential Test, and Eysenck's Personality Inventory. This research was aimed to analyze the ability of the tests for predicting students' achievement in the form of GPA semester I and || along their first year by doing a cohort study. There were 70 students eligible for the analysis and SPSS for windows software was used to do the analysis. The results show that TOEFL may still be used as one of the se- lection instrument because the yielded scores had moderate relationship with GPAS. Meanwhile, Academic Potential test is strongly suggested to be kept as the primary instrument because its strong power in predicting student achieve- ment. On the other hand, personality assessment is advised to be dropped since its relationship with GPA was too weak.